A new subspecies of Stachys cretica (Lamiaceae) from western Turkey - Akçi̇çek, Ekrem; Güner, Özal (Phytotaxa, 2022)
A new subspecies of Stachys cretica (Lamiaceae) from Turkey, Stachys cretica subsp. gulendamiana, is described and its relationships with allied subspecies is discussed. The new subspecies is characterized by having decumbent flowering stems. Stachys cretica subsp. gulendamiana is similar to S. cretica subsp. anatolica, but it differs mainly by its marine sandy habitat, indumentum adpressed white lanate—tomentose, flowering stems decumbent, basal leaves undulate, nutlets dull, greyish—brown. IUCN threat category, geographical distribution map and ecology of the new subspecies are also given.